Specific emotion regulation difficulties mediate the relationship between personal distress and depressive symptoms in medical students - Colonnello, Valentina; Castellano, Paola; Mazzetti, Michela; Russo, Paolo Maria (Frontiers in Psychology, 2024)
Several studies indicate a link between personal distress and vulnerability to depression. The literature also suggests that personal distress is associated with emotion dysregulation and that emotion dysregulation plays a role in depression. However, which of the various emotion regulation difficulties mediates the relationship between personal distress and depression remains unexplored. This study therefore aims to investigate the mediating role of specific emotion regulation difficulties in the relationship between personal distress and depression. Of the 702 initially recruited participants, 635 completed a survey comprising the Interpersonal Reactivity Index, the Difficulties in Emotion Regulation Scale, and the Beck Depression Inventory. A mediation analysis was used to explore which emotion regulation difficulties mediate the relationship between personal distress and depression. Over a quarter (27%) of participants reported moderate-severe depression symptoms. Difficulties in accessing adaptive emotion regulation strategies and in having a clear understanding about one's own emotions partly mediated the relationship between personal distress and depression symptoms. Our results are the first to indicate that personal distress is linked to depression risk through specific emotion regulation difficulties in medical students. They also highlight possible modifiable skills that could be targeted by prevention intervention.